Occurrences of extreme solar irradiance at 3812 meters above sea level, at Lake Titicaca (Puno - Peru) [Ocurrencias de Irradiancia Solar Extrema a 3812 m.s.n.m., a nivel del Lago Titicaca (Puno - Perú)] - Cutipa J.M.R. (2020)
The capture of the solar resource by means of photovoltaic systems to transform it into electricity depends on the solar irradiance during the day and climatic factors, the latter being of great importance. Aiming at evaluating and determining the occurrences of extreme solar irradiance and the Peak Sun Hours (HSP) in varied climatic conditions of the altiplano at 3812 meters above sea level, at the level of Lake Titicaca (Puno - Peru) and its effects on the photovoltaic system. The solar irradiance measurement was performed with two short-circuit photovoltaic modules each, where the Isc short-circuit current was connected to a current transducer to convert it into an analog electrical signal processed and stored every second in a programmable Logic Controller High precision (PLC). The results show the occurrence of extreme solar irradiance exceeding 1000 W / m2 and the solar constant for a few seconds on partially cloudy days, determining that the HSP is above 6 kWh / m2 / d and its effects on the photovoltaic system. Finally, in the Puno Altiplano, over irradiance is caused by the interaction of the clouds around the sun and the transitory presence of rain in short periods of time that affects the electrical protection system of a photovoltaic system. © 2020 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.